2019
DOI: 10.7556/jaoa.2019.121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Osteopathic Cranial Manipulative Medicine on an Aged Rat Model of Alzheimer Disease

Abstract: Context In the aging brain, reduction in the pulsation of cerebral vasculature and fluid circulation causes impairment in the fluid exchange between different compartments and lays a foundation for the neuroinflammation that results in Alzheimer disease (AD). The knowledge that lymphatic vessels in the central nervous system play a role in the clearance of brain-derived metabolic waste products opens an unprecedented capability to increase the clearance of macromolecules such as amyloid β pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…This finding is consistent with a pre-clinical study by Tobey and colleagues who investigated the effect of cOMM on improving the conditions related to AD, such as attenuating amyloid-β levels and reducing levels of activated astrocytes. 57 Aged AD animals received cOMM every day for 7 days, with histological analysis revealing an increase in GFAP expression in the DG subregion, which was also observed in this pilot study. Tobey and colleagues hypothesized that with the increased circulation of fluid as a result of the cOMM treatment, astrocytes could be directly involved in these waste clearance mechanisms.…”
Section: Discussionsupporting
confidence: 80%
“…This finding is consistent with a pre-clinical study by Tobey and colleagues who investigated the effect of cOMM on improving the conditions related to AD, such as attenuating amyloid-β levels and reducing levels of activated astrocytes. 57 Aged AD animals received cOMM every day for 7 days, with histological analysis revealing an increase in GFAP expression in the DG subregion, which was also observed in this pilot study. Tobey and colleagues hypothesized that with the increased circulation of fluid as a result of the cOMM treatment, astrocytes could be directly involved in these waste clearance mechanisms.…”
Section: Discussionsupporting
confidence: 80%
“…The interest in nontraditional medicine and alternative techniques for symptom relief is not a new interest. Dating back to the 20th century, Abraham Flexner wrote about the addition of osteopathic medicine to scientific education and research [ 48 ]. Flexner’s thoughts about integrating additional medical techniques into education have been influential to modern medical teachings and become part of the curricula and values taught by medical education.…”
Section: Cranial Osteopathymentioning
confidence: 99%
“…Observational studies have shown a reduction in symptoms associated with dementia [13] and multiple sclerosis [14]. Studies have also shown that OCMM affects cerebral blood ow [15,16], tissue oxygenation in prefrontal lobes [17], brain cortex electrical activity [18] and reduction in Amyloid beta (Aβ) protein levels [19,20]. How might OCMM produce these effects?…”
Section: Main Textmentioning
confidence: 99%